2021
DOI: 10.1111/rda.13999
|View full text |Cite
|
Sign up to set email alerts
|

First successful frozen semen of the maned wolf (Chrysocyon brachyurus)

Abstract: The maned wolf (Chrysocyon brachyurus, Illiger 1815) is the largest canid in South America, with an estimated population of approximately 20,000 concentrated individuals, mainly (90%) in Brazil. On the International Union for Conservation of Nature-IUCN website, the maned wolf is listed as Near Threatened. The ex situ populations have low reproductive efficiency (Songsasen et al., 2006), and several challenges remain, including the need for basic research on reproduction and assisted breeding in captivity (Pau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The difficulty of obtaining ejaculates in South American canids has been overcome in Maned wolf ( 83 , 114 ) and Crab-eating fox ( 103 ) using seminal collection by digital stimulation of the penis, similar to what is done in domestic dogs. This approach has already allowed seminal characterization in captive Crab-eating fox ( 103 ) and Maned wolf ( 83 ), determination of sperm seasonal changes ( 83 ), and cryopreservation of seminal samples ( 114 ) in Maned wolf. It is worth noting that this technique required prior conditioning of the Crab-eating fox ( 103 ) and safety precautions since the animals are neither sedated nor anesthetized.…”
Section: Reproductive Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty of obtaining ejaculates in South American canids has been overcome in Maned wolf ( 83 , 114 ) and Crab-eating fox ( 103 ) using seminal collection by digital stimulation of the penis, similar to what is done in domestic dogs. This approach has already allowed seminal characterization in captive Crab-eating fox ( 103 ) and Maned wolf ( 83 ), determination of sperm seasonal changes ( 83 ), and cryopreservation of seminal samples ( 114 ) in Maned wolf. It is worth noting that this technique required prior conditioning of the Crab-eating fox ( 103 ) and safety precautions since the animals are neither sedated nor anesthetized.…”
Section: Reproductive Characteristicsmentioning
confidence: 99%
“…The use of dimethyl sulfoxide resulted in higher post-thawing motility (20.0 ± 1.9 vs. 13.5 ± 2.1%) and plasma membrane integrity (51.2 ± 1.7 vs. 41.5 ± 2.2%) than glycerol ( 111 ). In the other study, conducted by our group, semen was frozen with a TRIS egg yolk extender containing 7% glycerol; post-thawing sperm motility was >55% ( 114 ). In other species of South American canids, there are apparently no reports on sperm cryopreservation.…”
Section: Reproductive Characteristicsmentioning
confidence: 99%
“…Over the years, numerous studies showed that it has been successfully used as a component of semen extenders for mammals, mainly bulls (Ashrafi et al, 2019; Ngoula et al, 2014), horses (El‐Badry et al, 2015), rams (Alcay et al, 2015; Marco‐Jimenez et al, 2004), boars (Selige et al, 2021) and dogs (Belala et al, 2019). Recent study has reported the first, great success in the preservation of maned wolf semen after the use of Tris‐yolk extender (Teodoro et al, 2021).…”
Section: Introductionmentioning
confidence: 99%